Validity and Reliability of the Timed Up and Go and the Anterior Functional Reach Tests in Evaluating Fall Risk in the Elderly - Mohamad Ali Aslankhani; Alireza Farsi; Zahra Fathirezaie; Seyed Hojjat Zamani Sani; Mohammad Taghi Aghdasi (Sālmand. (Tihrān), 2015)
Objectives The purpose of this study was to investigate the validity and reliability of Timed Up and Go (TUG) and Functional Reach (FR) tests in evaluating fall risk in the elderly. Methods & Materials 200 elderly were equally divided into falling or no falling history groups. The participants were community-dwelling adults aged 60 years and over in Tehran, Iran. All subjects performed TUG and FR tests. Data were analyzed using Pearson's correlation, ANOVA, Cronbach's alpha and t tests. Results TUG test had acceptable construct validity (Group difference, growth and clinical validity), Cronbach's alpha was 0.81 and time stability was 0.98. Also, FR test had acceptable construct validity (Group difference, growth and clinical validity) and time stability (0.97). Results showed that TUG and FR tests have significant correlations with fall risk. Conclusion TUG and FR tests have acceptable validity and reliability for the elderly. Therefore, these two tests can be used to identify possible fall risk in elderly.